2002
DOI: 10.1177/088626002237854
|View full text |Cite
|
Sign up to set email alerts
|

Using Demographic Risk Factors to Explain Variations in the Incidence of Violence Against Women

Abstract: This article offers statistical support for the contention that demographic risk factors influence the incidence of some women's experiencing violence more than others. Our results were generated using a binary probit model and 6,332 observations from the 1996 Australian Women's Safety Survey. For purposes of comparison, we identified a set of benchmark demographic characteristics as those occurring most frequently in the data set and estimated that if a woman were to have all of these characteristics, the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 33 publications
7
31
2
Order By: Relevance
“…Our finding that postcodes with greater linguistic diversity experience lower rates of police-recorded domestic violence is contrary to the expectations of social disorganisation theory, but consistent with non-ecological surveys in Australia (Mouzos & Makkai, 2004;O'Donnell, Smith, & Madison, 2002). Contrary to our expectations, postcodes with a greater female income share also had elevated rates of violence.…”
Section: Accepted Manuscriptcontrasting
confidence: 85%
“…Our finding that postcodes with greater linguistic diversity experience lower rates of police-recorded domestic violence is contrary to the expectations of social disorganisation theory, but consistent with non-ecological surveys in Australia (Mouzos & Makkai, 2004;O'Donnell, Smith, & Madison, 2002). Contrary to our expectations, postcodes with a greater female income share also had elevated rates of violence.…”
Section: Accepted Manuscriptcontrasting
confidence: 85%
“…O’Donnell, Smith, and Madison (2002) found that lower income was associated with greater MFPV. Pan, Neidig, and O’Leary (1994) found that any MFPV was associated with lower income, and that severe MFPV was associated with lower income than mild MFPV.…”
Section: Resultsmentioning
confidence: 94%
“…In cross-sectional work, O’Donnell et al (2002) found higher risk for MFPV victimization among separated and divorced women versus married women. Hyman, Forte, Mont, Romans, and Cohen (2006) found for the CGSS examining MFPV and victimization that the strongest risk factor for IPV was marital status, with women who were single, divorced, separated, or widowed being 10 times more likely to report IPV as compared to women who were married or living with a common-law partner.…”
Section: Relationship Risk Factorsmentioning
confidence: 93%
“…Beyond the victimoffender relationship, researchers have focused on correlates of non-lethal victimization among women, including age, race, education, income, employment, and prior victimization. Although some studies have found that younger women are at a higher risk for victimization than older women (O'Donnell, Smith, & Madison, 2002;US Department of Justice, 1998) and African American women are more likely than any other group of women to experience intimate partner violence (US Department of Justice, 2000b), this relationship between race and risk for victimization disappears once other individual and community level factors are included (Lauritsen & White, 2001). Prior victimization, including experiencing abuse as a child, has been associated with an increased risk for subsequent victimization (Gidycz, Hanson, & Layman, 1995;Mandoki & Burkhart, 1989;Stermac, Reist, Addison, & Millar, 2002).…”
Section: Correlates and Risk Factors Of Victimizationmentioning
confidence: 97%
“…recognize marginalized female populations as a group that has a significantly higher risk of victimization. Within general populations, studies have examined a wide array of behavioral processes, situational contexts, and other correlates associated with violence and victimization of women, including victim precipitation (Amir, 1971;Gelles, 1979), violence between spouses and intimates (Fagan & Browne, 1994; US Department of Justice, 2000a), victim-offender overlap (Klevens, Duque, & Ramirez, 2002;Lauritsen, Sampson, & Laub, 1991;Sampson & Lauritsen, 1990), as well as the distribution of violence across groups of women (Browne, Miller, & Maguin, 1999;Dugan & Apel, 2003;Mustaine & Tewksbury, 2002;Vogel & Himelein, 1995;Wenzel, Leake, & Gelberg, 2001), and across demographic groups (Lauritsen & White, 2001;O'Donnell, Smith, & Madison, 2002). The most recent advancement is the multi-level examination of relationships among individual, family, and community correlates of a women's victimization (Lauritsen & Schaum, 2004;Van Wyk, Benson, Fox, & DeMaris, 2003).…”
Section: Introductionmentioning
confidence: 99%